Effectiveness of a simulated patient training programme based on trainee response accuracy and appropriateness of feedback. (23rd February 2014) - Yoshida, T.; Ogawa, T.; Taguchi, N.; Maeda, J.; Abe, K.; Rodis, O. M.; Nakai, Y.; Shirai, H.; Torii, Y.; Konoo, T.; Suzuki, K.
Abstract Introduction Simulated patients (SPs) need education and training in required skills to be effective resources in education. This study was conducted to examine the effectiveness of an SP training programme based on the accuracy of trainee responses and the appropriateness of their feedback. Methods Thirty‐two applicants to the training programme and 35 experienced SPs were included in this study. The experienced SPs served as a reference group. The rate of accurate responses and the rate of appropriate feedback were assessed with pre‐ and post‐training tests, and these two outcome measures were compared with those of the experienced SPs. Results No significant differences were found in trainee response accuracy or appropriateness of feedback between pre‐ and post‐training tests. The response accuracy rate of the trainees on the pre‐training test was significantly lower than that of SPs with 1–2 years of experience, whilst there was no significant difference between these SPs and the trainees on the post‐training test. Conclusions Although our study suggests that more training is needed to improve the skills of SPs, the training programme may contribute to helping trainees reach a novice level in the skill of providing accurate responses. SP training should be encouraged to contribute to the effectiveness of such teaching and to establish the validity of the assessment.